1999
DOI: 10.1080/08990229970357
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of experimental pruritus and mechanically evoked dysesthesiae with local anesthesia

Abstract: Pain reduces itch-a commonly known effect of scratching the skin. Experimentally produced itch from histamine is sometimes accompanied by secondary sensations of pain. The present study investigated the effects of eliminating this pain, by means of a local anesthetic, on the itch and the enhanced mechanically evoked itch and pain that occur after an intradermal injection of histamine. In ten human subjects, the volar forearm was injected with either 20 microl of 2% chloroprocaine (experimental arm), or 20 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
8

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 19 publications
2
69
0
8
Order By: Relevance
“…Second, pruriceptors can respond to an allogeneic stimulus, but activation of a larger number of pain-specific fibers can dominantly mask itch (16,86). Indeed, an antagonistic relationship between pain and itch has long been recognized (11,(88)(89)(90)(91). Over 80 years ago, Lewis found that itch evoked by histamine injection can be suppressed by electric stimuli (88).…”
Section: The Coding Of Pain Versus Itchmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, pruriceptors can respond to an allogeneic stimulus, but activation of a larger number of pain-specific fibers can dominantly mask itch (16,86). Indeed, an antagonistic relationship between pain and itch has long been recognized (11,(88)(89)(90)(91). Over 80 years ago, Lewis found that itch evoked by histamine injection can be suppressed by electric stimuli (88).…”
Section: The Coding Of Pain Versus Itchmentioning
confidence: 99%
“…Mechanistically, scratching, a painful stimulus, can directly silence the firing of histamine-sensitive neurons in the spinal cord (91). Conversely, an inhibition of pain can enhance histamine-induced itch (90), and itch is a common side effect of analgesic treatment with opioids (11).…”
Section: The Coding Of Pain Versus Itchmentioning
confidence: 99%
“…Although most experimental studies of itch use histamine as the pruritic stimulus (Simone et al, 1987;Schmelz et al, 1997;Atanassoff et al, 1999), clinical pruritus is not typically mediated by histamine (Klein and Clark, 1999;Steinhoff et al, 2003). Therefore, the identification of compounds that elicit a strong histamine-independent itch would provide a tool with which to search for novel itch receptors and endogenous ligands.…”
Section: Introductionmentioning
confidence: 99%
“…An intradermal injection of histamine induces hyperalgesia (enhanced prickling pain) and hyperknesis (enhanced pricking-evoked itch), and intradermal pretreatment with the local anesthetic chloroprocaine produces the inhibition of pain and the enhancement of itch. 11) In contrast, itch sensation is generally reduced by pain produced by scratching. Therefore, it was suggested that itch produced by intrathecal and epidural injection of mu-opioid receptor agonists in humans is due to the inhibition of pain input by opioids in the dorsal horn.…”
mentioning
confidence: 99%